2020
DOI: 10.1111/bjet.13022
|View full text |Cite
|
Sign up to set email alerts
|

Immersive virtual reality for supporting complex scientific knowledge: Augmenting our understanding with physiological monitoring

Abstract: Her research interests span the fields of learning sciences, humancomputer interaction, technology-enabled learning, science inquiry and computer-supported collaborative learning, with an emphasis on immersive environments. Rhonda McEwen is an associate professor and director of ICCIT at UTM. She is a Canada Research Chair in Tactile Interfaces, Communication and Cognition. Her research combines communication studies, applied and behavioral sciences to examine the social and cognitive effects of technologies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Comparisons between VR and desktop virtual environment showed that VR works well in teaching abstract subjects such as memory management and allocation in computer science. Similar results are achieved by Lui et al [26] in science education.…”
Section: Literature On Immersive Vr Education Applicationssupporting
confidence: 90%
“…Comparisons between VR and desktop virtual environment showed that VR works well in teaching abstract subjects such as memory management and allocation in computer science. Similar results are achieved by Lui et al [26] in science education.…”
Section: Literature On Immersive Vr Education Applicationssupporting
confidence: 90%
“…In summary, seven of the 31 studies comparing a VR group and another technology/method/control group included significant differences/changes that favoured the HMD-VR group (Agrawal et al, 2018;Freitas et al, 2020;Gutierrez et al, 2007;Liu et al, 2020;Lui et al, 2020;Ou et al, 2021;Parmar et al, 2016). In three studies, the technology/method/control group yielded better results than the HMD-VR group (Lai et al 2021;Makransky et al, 2019;Moreno & Mayer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 26 of the studies were published in journals, while the remaining 11 studies were published in conference proceedings. In addition, as the time scope of the studies was so wide, we could not tell whether the improved learning outcomes from VR use were caused by the superiority of VR or improvements in the VR technology over the years -most studies concluding that HMD-VR yields better outcomes than comparison groups are published in recent years (Agrawal et al, 2018;Freitas et al, 2020;Gutierrez et al, 2007;Liu et al, 2020;Lui et al, 2020;Ou et al, 2021;Parmar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Participants correctly evaluated statements about object details in 50% of the trials. A recent study by Lui et al suggests that processing of spatial information in IVR is related to cognitive costs 39 . The authors found improved learning in a seated IVR learning experience, however not in a free moving IVR experience, when compared to a control condition (no IVR experience).…”
Section: Discussionmentioning
confidence: 99%